2019
DOI: 10.1021/acs.est.9b06139
|View full text |Cite
|
Sign up to set email alerts
|

Chlorine Isotope Fractionation of the Major Chloromethane Degradation Processes in the Environment

Abstract: Chloromethane (CH 3 Cl) is an important source of chlorine in the stratosphere, but detailed knowledge of the magnitude of its sources and sinks is missing. Here, we measured the stable chlorine isotope fractionation (ε Cl ) associated with the major abiotic and biotic CH 3 Cl sinks in the environment, namely, CH 3 Cl degradation by hydroxyl ( • OH) and chlorine ( • Cl) radicals in the troposphere and by reference bacteria Methylorubrum extorquens CM4 and Leisingera methylohalidivorans MB2 from terrestrial and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
29
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(30 citation statements)
references
References 77 publications
0
29
1
Order By: Relevance
“…However, microorganisms living in close association with these plant hosts might substantially mitigate fluxes of CH 3 Cl into the atmosphere. In this context, recent isotopic mass balances of atmospheric CH 3 Cl, including isotopic analysis of carbon (Bahlmann et al, 2019), hydrogen (Keppler et al, 2018) and chlorine (Keppler et al, 2019), point to large unidentified terrestrial sinks and sources of CH 3 Cl. The present study reveals the complexity of CH 3 Cl budgetassociated processes.…”
Section: Discussionmentioning
confidence: 99%
“…However, microorganisms living in close association with these plant hosts might substantially mitigate fluxes of CH 3 Cl into the atmosphere. In this context, recent isotopic mass balances of atmospheric CH 3 Cl, including isotopic analysis of carbon (Bahlmann et al, 2019), hydrogen (Keppler et al, 2018) and chlorine (Keppler et al, 2019), point to large unidentified terrestrial sinks and sources of CH 3 Cl. The present study reveals the complexity of CH 3 Cl budgetassociated processes.…”
Section: Discussionmentioning
confidence: 99%
“…However, microorganisms living in close association with these plants might substantially mitigate the emission of CH3Cl into the atmosphere. In this context, recent isotopic mass balances of atmospheric CH3Cl including isotopic analysis of carbon [115], hydrogen [116] and chlorine [117] Acknowledgments: EK gratefully acknowledges support through the DFG. FB acknowledges the Bio-Informatic MicroScope platform at Evry (France) for annotation and comparative analysis of MAGs.…”
Section: Discussionmentioning
confidence: 99%
“…For future studies, incubations under lower, environmentally observed concentrations (~600 pptv), coupled with targeted proteomics and/or transcriptomics approaches, may help to identify as yet unidentified CH3Cl degradation pathways. Finally, the application of triple element isotope analysis [117] might provide clues on the global relevance of vegetation and their associated microbes in mitigating emissions of CH3Cl to the atmosphere.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The role of atmosphere‐surface interactions in determining the variation and present values of δ 37 Cl on Mars is an outstanding scientific question, which can only be solved by atmospheric measurements supporting existing modeling efforts. While on Earth these dynamics are well studied (e.g., Keppler et al., 2020; Laube et al., 2010), there is no definite explanation of the peculiarly “light” Cl isotopic composition found at Mars’ surface. The widespread observation of perchlorates by the Phoenix lander (Hecht et al., 2009) and by the sample analysis at Mars (Mahaffy et al., 2012) onboard Curiosity rover (Glavin et al., 2013) suggested mechanisms similar to those in place for the Atacama perchlorates.…”
Section: Introductionmentioning
confidence: 99%